(untitled) (Fiep Bulletin - online, 2013)
In the contribution authors deal with research of attitudes to performance movement activities of Bratislava university students (Slovakia). By questionnaire method (606 respondents) were used Lickert scale of summed estimations that is statistically and logically evaluated. Authors found the most significant differences between students of Faculty of physical education and sport with other faculties students (same for boys and girls) in attitude components tendency to act and cognitive; slighter smaller difference was found in emotion component.